Genetic divergence, path coefficient and cluster analysis of ricebean (Vigna umbellata) genotypes in the mid-altitudes of Meghalaya - DEVI, YENGKHOM SANATOMBI; PANDEY, AVINASH; KUMAR, AMIT; ANSARI, M A; TYAGI, WRICHA; RAI, MAYANK; DAS, ANUP (The Indian Journal of Agricultural Sciences, 2018)
One hundred and twenty germplasm of ricebean [Vigna umbellata (Thunb) Ohwi and Ohashi] were evaluated during 2015-16 and 2016-17 to study the yield related traits in ricebean in the mid-altitudes of Meghalaya. Luxuriant ricebean growth with a wide spectrum of variability for plant height, number of branches per plant, days to flowering, number of pods per plant and 100 seed weight was observed. The genotypic variance was moderate to high for the said characters which resulted in moderate to high heritability and genetic advance values. Grain yield/plant was positively and significantly correlated with number of clusters per plant, number of pods per plant and 100 seed weight. Moderateto high heritability and the genetic advance of these plant characters vis-a-vis their positive association and direct positive effect on grain yield/plant suggested for their consideration during selection of high yielding genotypes. All the tested ricebean genotypes could be grouped into seven distinct clusters. An analysis of the percentage contributionof individual characters towards genetic diversity revealed that 100-seed weight and days to 80% maturity, days to 50% flowering were the major characters contributing to genetic diversity in ricebean. Based on the results we found genotype CHAK HAWAI-2 may be used as parent for developing long pod with bold seed cultivar. Genotype ChakHawai-31 may be used as parent for developing high yielding genotypes. Genotype BKSB-23 had less bold seed but, high yield and may be used as parent for developing small seed and high yielding variety.